2012
DOI: 10.1007/978-3-642-35142-6_4
|View full text |Cite
|
Sign up to set email alerts
|

Action Design Ethnographic Research (ADER): Vested Interest Networks and ICT Networks in Service Delivery of Land Records in Bangladesh

Abstract: Abstract. Identifying rigorous and relevant research methods has for a long time been a challenge in IS research. This is amplified in developing countries, where understanding the context is key. This paper presents an Action Design Research based approach, incorporating ethnography, which aims to provide a more authentic and relevant analysis. The Action Design Ethnographic Research (ADER) method is illustrated through the case of ICTs and land records management in Bangladesh. The findings show that where I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2013
2013
2014
2014

Publication Types

Select...
2
1

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…Finally, in previous work we have showed that within the ADR processes and principles, there have already appeared ethnographic approaches in ADR (Alam, Brooks and Khan 2012). ADR seeks external and internal perspectives for mutual reciprocal relations in redesigning artifacts through ongoing use (Sein et al 2011) .…”
Section: Action Research (Ar) -Design Research (Dr) -Ethnographic Resmentioning
confidence: 93%
See 1 more Smart Citation
“…Finally, in previous work we have showed that within the ADR processes and principles, there have already appeared ethnographic approaches in ADR (Alam, Brooks and Khan 2012). ADR seeks external and internal perspectives for mutual reciprocal relations in redesigning artifacts through ongoing use (Sein et al 2011) .…”
Section: Action Research (Ar) -Design Research (Dr) -Ethnographic Resmentioning
confidence: 93%
“…One approach is to draw methodological contributions from reference disciplines with a view to investigating complex issues (Thompson 2012). At the same time, IS scholars have been relentlessly striving to develop innovative methodologies, for example, action research in IS (Baskerville 1999b), canonical action research (Davison et al 2004), design research (Hevner et al 2004), action design research (ADR) (Sein et al 2011), participatory action design research (Bilandzic and Venable 2011) and action design ethnographic research (ADER) (Alam, Brooks and Khan 2012). Among these, ADR has emerged as a significant approach, for example by its publication in MIS Quarterly (one of the top journals of the discipline (Sein et al 2011)).…”
Section: Introductionmentioning
confidence: 99%
“…Thus E-service has emerged as a potential field, focusing on designing and redesigning IT and organizational processes of public sector organization. Although every government is striving to deliver E-services successfully, many developing countries have failed to provide effective and efficient E-service for their citizens [1], [2], [28], [45].…”
Section: Psis For E-service In Public Sector Organizationmentioning
confidence: 99%
“…However, focuses on the context of public sector organizations and process of service delivery in public sector organization require particular attention due to the nature and wide of public service delivery. Particularly, public sector organizations in many developing countries carry thick bureaucratic processes and heritage from colonial legacies, vested interests of staff and decision makers, rigidity in statutes and structure of organizations [2], [5], [20], [21]. Consequently, designing and implementing E-service in public sector organizations demands more in-depth and wider approach, tools and skills.…”
Section: Introductionmentioning
confidence: 99%